TREATMENT MANAGEMENT OF SEXUALLY TRANSMITTED INFECTION AMONG FEMALE SEX WORKERS IN THE SARIREJO LOCALIZATION, SALATIGA, INDONESIA - Reny Eka Saputri; Rose Nurhudhariani; Lestari Puji Astuti (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Salatiga Public Health Office stated that sexual infection in 2013 was 1,096 cases. While 1,085 cases were recorded between January until November 2014. The sexually transmitted infection rate in Sidorejo Lor Health Center has increased from 96 in 2013 to 133 cases in 2014. Although the screening program already exists, but in the field cases of sexually transmitted infections are continue to rise. Aims: It aims to explore the efforts of sex workers to the sexually transmitted infection treatment, the way they do their activities without transmitting the infection to the customers, and the supports from the localization manager and medical workers for the treatment management for sexually transmitted infections of the sex workers. Method: This research used qualitative method. The data was obtained through in-depth interview. This study involved 3 women who are positively diagnosed with sexually transmitted infection in the Sarirejo localization, Salatiga, Indonesia. Results: The study highlights that the the sex workers who diagnosed with sexually transmitted infection seeks medical treatment from medical workers. Some drink herbs and wash their vagina with betel. During the treatment, they reduce their sex activity and always use condom. As realised the infection, they receive support from the localization manager and medical workers. Conclusion: From this study, we noted that female sex workers who realized having sexually transmitted infections will look for either medical and traditional treatment. Support from localization manager to managing STIs are reminded to always use condoms and participated the screening by Primary Health Care officers. Regulation issued by the provider and screening participation highlighted the treatment management of sexually transmitted infection among female sex workers in Salatiga, Indonesia.